New records of deep-sea Gastrotricha and Tardigrada from Iberian and Canary Basins (Northeast Atlantic) with comments on abyssal meiofauna composition and the meiofauna paradox - Trokhymchuk, R.; Kieneke, A. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
The “meiofauna paradox” refers to the amphi-oceanic or even cosmopolitan distribution of species of this ecological group, i.e. the marine meiofauna, as opposed to their weak dispersal potential. Dissolving this paradox includes on the one hand the discovery of complexes of genetically distinct but morphological cryptic species with much more limited distribution areas, but also involves the investigation of “stepping stone habitats” like the shelf area of oceanic islands and summits of seamounts. Such biotopes subdivide long distances, e.g. from one continent to the other, into shorter sections. However, what needs to be excluded is a possible distribution of “shallow water meiofauna” simply via population growth and range expansion at the abyssal plains of the world's oceans. In order to test if the abyssal plains may represent a barrier against dispersal of certain marine meiofauna taxa, we studied the composition of the meiofauna from six samples (stations) taken during the expedition IceDivA (SO280) of the R/V Sonne to the Iberian and Canary Basins from abyssal depths (4904-5485 m). The taxonomic focus was put on the Gastrotricha and Tardigrada. The dominant taxa in all samples were nematodes (13.0 - 97.7 ind./cm2) and copepods (0.4 - 9.6 ind./cm2), followed by annelids, kinorhynchs and ostracods. Three Gastrotricha species (Desmodasys sp. iberianA, Desmodasys sp. langsethA, Musellifer sp. iberianA (Musellifer aff. tridentatus)) and one tardigrade (Coronarctus dissimilis) were registered and examined using light microscopy (DIC and CLSM) and SEM. All gastrotrichs from the examined samples presumably represent new and still undescribed species. The range of geographic and bathymetric distribution of Coronarctus dissimilis increases to the Iberian Basin and to a depth of 4163 m. This finding further hints to a potential amphi-Atlantic distribution of this species. We compare our data with those from other studies on seamounts, oceanic islands and from the deep-sea and conclude that the abyssal plains represent a significant barrier against long distance dispersal for most genera (and species) of Gastrotricha and for a certain fraction of genera of Tardigrada, too.